MAHASISWA PGMI UIN GUSDUR SEBAGAI GURU LES: PELUANG DAN TANTANGAN EDUPRENEUR DALAM PENDIDIKAN DASAR - Adibatul Kamila; Bagus Arda Kamal; Nadlirul Ijmal (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
This study highlights the phenomenon of edupreneurship among PGMI UIN Gusdur students who act as private tutors. Edupreneurship is defined as the application of entrepreneurial values ​​in the educational realm so that students become not only scientists but also entrepreneurs in the educational field. The research method used is descriptive qualitative with data collection techniques through interviews and literature studies. The results show that PGMI students have a great opportunity to develop edupreneurship potential, particularly through private tutoring activities that serve as a means of teaching practice, developing managerial skills, and increasing practical experience. However, a number of challenges such as limited capital, time management, emotional control, and maintaining consistency in entrepreneurship remain obstacles. Therefore, edupreneurship among PGMI students needs to be managed strategically to become a means of developing the character of independent, innovative, and entrepreneurial educators.